2012
DOI: 10.3402/ijch.v71i0.19769
|View full text |Cite
|
Sign up to set email alerts
|

No association between temperature and deaths from cardiovascular and cerebrovascular diseases during the cold season in Astana, Kazakhstan – the second coldest capital in the world

Abstract: BackgroundSeveral European and North American studies have reported associations between cold temperatures and mortality from diseases of the circulatory system. However, the effects of cold vary between the settings warranting further research in other parts of the world.ObjectivesTo study associations between temperature and mortality from selected diseases of circulatory system in Astana, Kazakhstan – the second coldest capital in the world.MethodsDaily counts of deaths from hypertensive diseases (ICD-10 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…This result is consistent with other investigations that revealed cold weather as responsible for the most part of the temperature-related CVD mortality ( Goggins et al, 2013 ; Xie et al, 2012 ; Yang et al, 2015c ). In contrast to our findings, Grjibovski et al (2012) in a study in Astana, Kazakhstan- the second coldest capital in the world between 2000–2001 and 2006–2010, didn’t find any significant associations between ambient temperatures and mortality of hypertensive diseases (ICD-10 codes: I10–I15), ischemic heart disease (I20–I25) and CVDs (I60–I69). The inconsistency between the findings may be due to differences in geographical location of studies and weather conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with other investigations that revealed cold weather as responsible for the most part of the temperature-related CVD mortality ( Goggins et al, 2013 ; Xie et al, 2012 ; Yang et al, 2015c ). In contrast to our findings, Grjibovski et al (2012) in a study in Astana, Kazakhstan- the second coldest capital in the world between 2000–2001 and 2006–2010, didn’t find any significant associations between ambient temperatures and mortality of hypertensive diseases (ICD-10 codes: I10–I15), ischemic heart disease (I20–I25) and CVDs (I60–I69). The inconsistency between the findings may be due to differences in geographical location of studies and weather conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, an interesting question to ask is how the sensitivity to cold will change in the Netherlands, as winters are anticipated to become milder. A study by Grjibovski et al [ 65 ] found no significant association between temperature and cardiovascular mortality in Astana, the second coldest capital in the world; they concluded that people living in such cold climates were just better adapted to cold (e.g., culture of wearing large volumes of winter clothes outdoors) than populations living in other regions. McMichael et al [ 20 ] found that sensitivity to cold tended to be higher in warmer cities such a Bangkok compared to colder cities like Bucharest, although the factors contributing to this difference could not be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between cause-specific cardiovascular mortality and ambient temperature in different areas still remains unclear. Only a few studies have examined the susceptibility of cause-specific cardiovascular mortality related to extreme temperatures [ 5 , 19 , 20 , 21 ]. Moreover, their results are inconsistent [ 5 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined the susceptibility of cause-specific cardiovascular mortality related to extreme temperatures [ 5 , 19 , 20 , 21 ]. Moreover, their results are inconsistent [ 5 , 21 ]. In addition, even in the same country, the impact of extreme temperatures differed by regional climatic types [ 22 ].…”
Section: Introductionmentioning
confidence: 99%